EFFECT OF PEOPLE'S BUSINESS CREDIT, EDUCATION LEVEL OF ENTREPRENEUR, AND ENTREPRENEURSHIP TO PRODUCTIVITY OF MICRO, SMALL, AND WINNING BUSINESS OF GIANYAR REGENCY - Putra, Ayudyas Dwi; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 8, Agustus 2018 (pp. 1587-1825), 2018)
Productivity is the output between output and input. To achieve maximum productivity, Micro, Small and Medium Enterprises (MSMEs) can utilize People's Business Credit (KUR), improve education, and need to have an entrepreneurial spirit. The purpose of this study is to analyze the effect of KUR, entrepreneurship education level, and entrepreneurship simultaneously and partially to UMKM productivity. This research was conducted at UMKM in all Regency of Gianyar. The number of samples in this study were 99 business units using proportionate stratified random sampling technique. Data collection method is done through questionnaire and theianalysis techniqueiused is multipleilineari regression. Basedion theiresults of theianalysis foundithat KUR, entrepreneurship level, and entrepreneurship simultaneously have a significant effecton UMKM productivity. Partially KUR, entrepreneurship education level, and entrepreneurship have positive and significant effect to UMKM productivity. Keywords: Micro, Small and Medium Enterprises (MSMEs), People's Business Credit, entrepreneurship education level, entrepreneurship, and productivity